Spatial and Temporal Planetary Boundary Layer Moisture‐Source Variability of Crimean Peninsula Precipitation - Langhamer, Lukas; Dublyansky, Yuri; Schneider, Christoph (Earth and Space Science, 2021)
This article was supported by the German Research Foundation (DFG) and the Open Access Publication Fund of Humboldt-Universität zu Berlin. The atmospheric water cycle is a key component of the global energy and moisture exchange. In order to gain better understanding of the atmospheric processes and temporal variability and trends affecting precipitation in Crimea, we use a Lagrangian moisture source detection technique based on reanalysis data from the European Center for Medium-Range Weather Forecasts. The study presents a quantitative picture of the major moisture sources that feed precipitation on the Crimean peninsula from February 1979 to January 2017. In total 51.3% of moisture stems from marine sources. Specifically, the main individual contributors are the Mediterranean Sea (15.3%), the Black Sea (14.4%), and the North Atlantic Ocean (13.9%). Continental moisture recycling contributes additional 46.9%. The amounts of moisture contribution from marine and continental sources and their respective moisture transport pathways are subject to strong seasonality. Winter precipitation in Crimea is predominantly sourced by the Mediterranean Sea. Long-term temporal trends in contribution from any of the major moisture sources are absent during the study period. Statistically significant negative correlation between the North Atlantic Oscillation (NAO) index and contribution from moisture sources exists in winter for the Mediterranean (R = −0.22) and Black Seas (R = −0.23), and for the southern continental moisture source (R = −0.37). The North Atlantic Ocean moisture source exhibits a statistically significant positive correlation with NAO index during spring (R = 0.32). German Research Foundation (DFG) Humboldt‐Universität zu Berlin Peer Reviewed